The role of place in shaping responsibility logics: Revisiting the relation between place and business sustainability - Verena Hermelingmeier; Karoline Augenstein; Alexandra Palzkill (Business Strategy and the Environment, 2022)
Place has been suggested to play a role for the sustainability orientation in business. A research gap exists in zooming in further on this relationship and in analysing how the organizational sense of place influences such an orientation. Applying the conceptual lens of institutional logics, we operationalize sustainability orientation as hybrid responsibility logic and analyse the role of place in the forming of such a logic. We present the results of a case study of businesses from a local sustainability network in the German city of Wuppertal and surroundings. Based on qualitative interview data, we found place to function as a coping mechanism in dealing with conflicting logics in the context of sustainability challenges. Across four heuristic types, we describe different roles of place in shaping responsibility logics: from providing the scenery for philanthropic engagement to being the nucleus for transformational efforts.
Keywords: 330; business sustainability; institutional logics; learning; sense of place; transformation; typology